Hubungan Antara Kompetensi Pengurusan Keusahawanan dengan Niat Inovatif Memulakan Perniagaan dalam Kalangan Pelajar di Universiti Tun Hussein Onn Malaysia (UTHM) - Nur Anis Allisya Afandi,; Anim Zalina Azizan, (Research in Management of Technology and Business, 2024)
In today's economy, students who want to venture into the field of entrepreneurship must have two of the most important things, which are entrepreneurial management skills and the desire to start a business in an innovative way. One of the ways to increase the innovative intention of starting a business is the communication skills that an individual has. This study is to examine the level of entrepreneurial management competence that triggers innovative ideas to start a business. Next, this study is also to examine the level of innovative intention to start a business as well as to examine the relationship between entrepreneurial management competence and innovative intention to start a business among students at Universiti Tun Hussein Onn Malaysia (UTHM). This study will use a questionnaire in the form of a Google Form. A total of 375 UTHM students completed the questionnaire which was distributed via WhatsApp and Telegram applications. The data of this study will be analyzed using Statistical Packages for Social Sciences (SPSS). SPSS application was also used to obtain descriptive analysis and correlation analysis. Descriptive analysis was used to determine mean values and standard deviations. Correlation analysis is to determine the normality of the data of this study using two research methods, namely visually and statistically. Finally, the results of the study found that there is a significant relationship between entrepreneurial management competence and the innovative intention to start a business among UTHM students.